Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2021)
With the 27th ORNAC National Conference now behind us, and the handover to a new ORNAC Executive complete, I would like to take this opportunity to thank Cathleen Ferguson for her dedication and leadership in completing a second term as President of ORNAC. This second term was not sought out by Cathleen but, rather, was taken on with a determination and a goal to bring ORNAC back to a fully volunteer run organization. Your leadership over the past two years has allowed ORNAC to continue to represent perioperative nurses across Canada, successfully launch two virtual AGMs, and now host a fully virtual conference. Our new strategic plan will continue to support our desire to remain volunteer driven as our Board Directors become ever more involved in the day-to-day business of running ORNAC and meeting its goals. Cathleen thank you… mission accomplished!